Government electronic services delivery and the digital divide: The case of Andhra Pradesh, India - Sundar Balakrishna (Asian Development Bank Institute (ADBI), 2018)
Despite garnering world-wide appreciation for her contribution to information technology services, India has to contend with serious issues relating to the digital divide. Beginning with a study of the various dimensions relating to the digital divide conceptually, the role of government services delivery in electronic form and its interactions with the digital divide are examined with reference to the Indian state of Andhra Pradesh. Using data from the office of Electronic Services Delivery, the findings reveal that there is considerable demand for government electronic services from rural and urban citizens in Andhra Pradesh, which in many ways contribute to narrowing the digital divide. Such services include land registration, driving licenses, utility payments, grievances registration and religion-oriented services. Econometric estimations show that the entrepreneurial spirit and competency of service providers, both in the urban and rural hinterland of the state, have a statistically significant and positive relationship with the number of e-government transactions therein. Contrary to the intuitive expectation that digitalization would facilitate trade, this study, through some key findings from the recent demonetization, shows that under certain conditions of information technology infrastructure paucity, digitization can constrict trade. One way out is to encourage cashless payment systems, whose implementation dynamics are touched upon. Some managerial implications are highlighted.
Keywords: O33; O38; 330; Andhra Pradesh; digital divide; electronic services; government; India